COMMUNITY SERVICE ACTIVITIES FOR DEVELOPMENT OF POTENTIAL TOURISM VILLAGES IN BALI (A STUDY BASED ON COMMUNITY SERVICE IN SIANGAN VILLAGE, GIANYAR) - I Made Sara , Komang Adi Kurniawan Saputra , Gde Deny Larasdiputra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In order to accelerate the Siangan Village of Gianyar Regency as a Tourism Village, the Faculty of Economics and Business, Warmadewa University, held Community Service and Student Social Service at Siangan Village, Gianyar. A tourism village is one of the concepts of developing the potential of an area that can be developed and makes a positive contribution to society. In building a tourist village, the important thing is a commitment between the government and village officials, community leaders, and village organizations to make the village a tourist village. The need for the role of academics to provide village tourism literacy to the assisted village communities is the background of this activity. SianganGianyar Village has the potential to be developed as a Tourism Village. Siangan Village has a lot of rich cultural heritage that needs to be raised and developed as a tourist attraction to improve the welfare of the people of Siangan Village and its surrounding villages.After determining the potential that the village has, then to become a tourist village, it must have tourism products or what is called a tourist destination. Destination is related to a place or area that has an advantage or characteristic to attract tourists. Characteristics can be geographically or culturally, such as mountains, sea, hills, savanna expanses, local culture such as local dances, traditional celebrations, and so on. To create a superior tourist destination, before a destination is introduced and sold like a tourist village, it must first assess the four main aspects that must be owned, namely Attraction, Accessibility, supporting facilities, and Ancillary. Tourist destinations as an attraction for tourists to visit and enjoy are very important to note because the selling value of tourist attractions is the destination.